Character Education: A Review of Implementation and Challenges in Schools - Asri; Deviv, Selvia (Cendekiawan Indonesia Timur, 2024)
Character education is an important effort in instilling moral and ethical values in the personality of learners, not only within the scope of school but also at home and society. In Indonesia, its implementation is faced with various challenges, including gaps in teachers' understanding, lack of resources, and student behavior that shows non-compliance with character values. Nonetheless, character education brings great opportunities in shaping individuals who are moral, responsible and have an awareness of the importance of tolerance and cooperation in society. Joint efforts between educators, parents and communities as well as strong policy support are needed to overcome barriers and strengthen character education to create an educational environment that supports the moral and ethical growth of Indonesia's young people.